2020
DOI: 10.24925/turjaf.v8i5.1090-1097.3282
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Phytochemical Activity of Coconut Shell Extracts

Abstract: Coconut shell extract contains phytochemical compounds tannins, saponins and steroids which are thought to act as antimicrobial compounds. This makes coconut shell extract has great potential as a natural preservative, one of which is the natural preservative coconut sap. This study aims to know the effect of coconut shell type, extraction time, extraction temperature and the combination of the three treatments on the antimicrobial activity and phytochemical extracts produced. This study using a Randomized Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The secang wood extract did not inhibit yeast growth in this study. This phenomenon was also reported by the research of Mazaya et al (2020), that no inhibition zones were formed by antibacterial compounds against yeast. This could be due to yeast having biochemical stability, the ability to spread quickly, resist autotoxicity (Periadnadi et al, 2018), and tolerate low pH between 3.5 and 4.5 (Mazaya et al, 2020).…”
Section: Microbiological Quality Of Kefirsupporting
confidence: 80%
“…The secang wood extract did not inhibit yeast growth in this study. This phenomenon was also reported by the research of Mazaya et al (2020), that no inhibition zones were formed by antibacterial compounds against yeast. This could be due to yeast having biochemical stability, the ability to spread quickly, resist autotoxicity (Periadnadi et al, 2018), and tolerate low pH between 3.5 and 4.5 (Mazaya et al, 2020).…”
Section: Microbiological Quality Of Kefirsupporting
confidence: 80%
“…The results of the phytochemical screening of U Groh coir and shell extract in this research contained the compounds flavonoids, tannins, and saponins. Young coconut shell extract was reported to contain the compounds tannins, saponins, and steroids (Mazaya et al, 2020). Conversely, (Wulandari et al, 2019), reported that coir ethanol extract from a young coconut contained the compounds tannins, phenols, and flavonoids.…”
Section: Phytochemical Screening Of Extractmentioning
confidence: 99%
“…The Maillard reaction can be inhibited by citric acid, which plays a role in lowering the pH [14]. The Maillard reaction is optimal in an alkaline situation [15].…”
Section: Figure 2 Reducing Sugar In Kepok Banana Flourmentioning
confidence: 99%